(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
An across geographical zone experiment was conducted to compare the performance of a riverine telferia accession with an upland land race in Awka. Both accessions seeds for planting were relatively of the same size and weight. At 21 days after planting, 77% of the riverine seeds emerged as against 72% of the local race. The Randomized Complete Block Design (RCBD) Experiment consisted of Upland and Riverine telferia accessions whole seeds as the treatments. They were each planted ten seeds on 4x1m beds (plots) and replicated five times. The riverine accession also produced more leaves, and longer vines at WAP1 and 2 before the two accessions leaf numbers and stem lengths became equal. The probable cause of its early start and better performance might be due to higher soil and environmental temperatures when compared with the relatively lower soil temperatures common in the riverine environment. The riverine accession also had the biggest vine girth and larger leaf area which accounted for its higher vine and leaf harvest at WAP 4 (213.70kg/ha) and WAP11 (4.00t/ha) as against upland accession WAP4 (77kg/kg) and WAP11 (2.68t/ha) harvests. Riverine accession started flowering early at 13 WAP (91 days), while upland accession started at 14 WAP (98days). Riverine accession also started fruiting at 16 WAP (112 days), while upland accession started fruiting at 23 WAP (161 days). Therefore, to achieve maximum production of telferia in Awka rainforest zone of Nigeria, riverine accession is recommended.